IDENTIFIKASI FUNGSI HUMAS KEMENTERIAN PARIWISATA DALAM IKLAN PARIWISATA â€œPESONA INDONESIAâ€ UNTUK MENINGKATKAN MINAT WISATAWAN NUSANTARA - N.R, Dwi Rakhmawati; Rochim, Achluddin Ibnu; Wibowo, Judhi Hari (representamen, 2017)
The Ministry of Tourism has started working on Indonesia‟s tourism campaign targetingdomestic tourists through tourism ads „Pesona Indonesia‟. In the tourism ads „Pesona Indonesia‟,public relation function is being applied by the Ministry of Tourism which related to theimplementation of growth and development in tourism interest.The public relation functions must be able to represent Indonesia‟s image which will be shown. Thisresearch is being done to identify the Ministry of Tourism‟s public relation functions in tourism ads„Pesona Indonesia‟ to increase domestic tourists‟ interest. The method used for the research isCharles Sanders Peirce‟s semiotics analysis, and the objects of the research is tourism ads „PesonaIndonesia‟ on television with Indonesia Milik Kita version, and event ads Festival Gentala Arasy 2017in pesona Indonesia travel official website. Based on the research that writer has done, it can beconcluded that the Ministry of Tourism applied the development of national tourism interest functionin tourism ads „Pesona Indonesia‟ Indonesia Milik Kita version by displaying tourism objects imageas a natural and cultural tourism area. But, it will be more potential if the concept that beingdisplayed is the uniqueness inside and around the tourism objects.Keywords : public relations, advertisement, tourism, semiotics